Modes of Teaching and Learning of Indigenous Music Using Methods and Techniques Predicated on Traditional Music Education Practice: The Case of Bapedi Music Tradition (European Journal of Education, 2019)
This paper takes a look at music education in Bapedi society in Sekhukhune district, Limpopo Province in South Africa as the transmission of musico-cultural manifestations from one generation to the other. The aim is to investigate the modes of transmission of indigenous Bapedi music. Music teaching and learning in Bapedi society is an integral part of cultural and religious life, and is rich in historical and philosophical issues. Traditional music knowledge system produces a better result to the teaching and learning of indigenous music in Bapedi culture. The research question of interest that emerges is: What are the modes of transmission for indigenous Bapedi music during the teaching and learning process? The primary source for data collection was oral interviews and observations. Secondary sources include theses, books and Journal articles. Performances were recorded in the form of audio-visual recordings and photographs. The results have shown that in Bapedi society, learning music through participation has been a constant practice. The transmission process involves participation, fostering of communal sense, concentration on the present moment and the use of musico-cultural formulae and cues for interactional purposes. It was concluded that in Bapedi society, creative music making and music identity are the obverse sides of the same coin, in that the former provides an arena in which the latter can be explored.